TIPSS for variceal bleeding in patients with idiopathic non‐cirrhotic portal hypertension: comparison with patients who have cirrhosis. Issue 7 (28th February 2019) - Lv, Yong; Li, Kai; He, Chuangye; Luo, Bohan; Zhang, Bojing; Liu, Haibo; Wang, Zhengyu; Guo, Wengang; Wang, Qiuhe; Chen, Hui; Bai, Wei; Yuan, Xulong; et al.
Summary: Background: In patients with idiopathic non‐cirrhotic portal hypertension (INCPH), the usual recommended strategy for management of variceal bleeding is the same as that in cirrhosis. However, this policy has been challenged by the different natural history between INCPH and cirrhosis. Aim: To compare outcomes after transjugular intrahepatic portosystemic shunt (TIPSS) between INCPH and cirrhotic patients admitted for variceal bleeding. Methods: Between March 2001 and September 2015, 76 consecutive patients with biopsy‐proven INCPH undergoing TIPSS for variceal bleeding in a tertiary‐care centre were included. 76 patients with cirrhotic portal hypertension receiving TIPSS for variceal bleeding, and matched for age, sex, Child‐Pugh class, stent type and index year of TIPSS creation served as controls. Results: Patients with INCPH, compared to those with cirrhosis, had significantly lower mortality (11% vs 36% at 5 years, adjusted HR, 0.37; 95% CI 0.15‐0.87, P = 0.022), overt hepatic encephalopathy (16% vs 33% at 5 years, adjusted HR, 0.35; 95% CI 0.16‐0.75, P = 0.007) and hepatic impairment, despite similar rates of further bleeding (33% vs 32% at 5 years, adjusted HR, 0.72; 95% CI 0.36‐1.44, P = 0.358), and shunt dysfunction (35% vs 36% at 5 years, adjusted HR, 0.84; 95% CI 0.41‐1.72, P = 0.627). These findings were consistent across different relevant subgroups. Conclusions: Patients with INCPH treated with TIPSS for variceal bleeding had similar progression of portal hypertension (further bleeding and shunt dysfunction) but fewer complications of liver disease (overt hepatic encephalopathy and hepatic insufficiency) and lower mortality rate compared with cirrhotic patients with comparable liver function.